Acute toxicity, biochemical and histological of fenitrothion and thiobencarb on fish Nile tilapia (Oreochromis niloticus) - Mohamed Riad Fouad; Ahmed Farahat El-Aswad; Maher Ibrahim Aly (Nusantara Bioscience, 2022)
Abstract. Fouad MR, El-Aswad AF, Aly MI. 2022. Acute toxicity, biochemical and histological of fenitrothion and thiobencarb on fish Nile tilapia (Oreochromis niloticus). Nusantara Bioscience 14: 217-226. The results show that the tested fenitrothion and thiobencarb are highly toxic to fish. However, fenitrothion is more toxic (1.6 times) on Oreochromis niloticus (Linnaeus, 1758) than thiobencarb. The determined 96-h LC50 values using a static bioassay system to Nile tilapia fingerlings (8-10 g) were 0.20 and 0.32 mg L-1 for fenitrothion and thiobencarb, respectively. The mortality rate of fish exposed to ½ 96-h LC50 of fenitrothion (0.10 mg/L) and thiobencarb (0.16 mg/L) for four days demonstrated was 20% mortality rate. Fish showed tremors, lethargy, decreased movement, and increased respiratory rhythm. The total activity of AChE in control was 5.61 ±0.03; it was significantly reduced to 4.92 ±0.03 in fenitrothion treatment and 1.13 ±0.02 in thiobencarb treatment. Fenitrothion decreased the specific activity from 0.83 ±0.01 for the control to 0.68 ±0.01, whereas thiobencarb reduced the specific activity to 0.22 ±0.01. Generally, thiobencarb inhibited AChE activity much more than fenitrothion; it produced 80% inhibition, while fenitrothion produced 12.5% inhibition. It showed a significant increase in liver GST and SOD activity of Nile tilapia exposed to the tested pesticides compared to the control. There were no histological alterations in the tissues of the control individuals. It was found that the herbicide thiobencarb affected the gills, kidneys, and liver of Nile tilapia more than the insecticide fenitrothion.